The Reputation Playbook: Exploring How Reputation Can Be Leveraged to Improve Recruiting Effectiveness in NCAA Men’s Basketball - Marshall J. Magnusen; Charn P. McAllister; Jun Woo Kim; Pamela L. Perrewé; Gerald R. Ferris (Journal of Applied Sports Management, 2017)
Reputation is a critical factor in the recruiting process. Organizational reputation also is a complex variable. Different dimensions of reputation may play very different roles in attracting recruits. In this study, a multidimensional (i.e., performance, character/integrity, support) reputation model is used to predict male basketball recruits’ university choice. Data were collected on the ESPN Top 100 male high school athletes recruited to NCAA Division I basketball programs for each year from 2010–2014 (n = 500). Probit regression analyses using maximum likelihood estimation predicted to what extent each reputation-based dimension affected the likelihood of an athlete selecting a university.
Keywords: Coaching; management; signaling; sport; student-athletes